Modelo relacional capacidade e demanda: investigando lesões musculares na coxa em atletas jovens de futebol - Natalia Franco Netto Bitencourt (2015)
Sports injuries are multifactorial and result from complex interactions between intrinsic and extrinsic risk factors. Studies assessing risk factors for sports injuries assume a direct relationship between exposure and outcome and the interactions between multiple predictors are evaluated by the sum of risk factors. Studies based on the traditional model described above have found inconsistent results because the model does not consider the complex nature of sports injuries. Specifically, it is not as simple as the sum of risk factors. Complex interactions are the influence (interdependence) between multiple factors related to the athletes capability of dealing with the mechanical energy (demands) originated by the sport. Additionally, the increased demand in a tissue could originate from anatomical structures distant from the tissue at risk. This fact could be explained due to interdependence between the body segments, which is inherent in the musculoskeletal system. Factors related to the pelvis, hip and foot (non-local) may contribute to the increase of energy demand in the thigh area and thus, can influence the occurrence of thigh muscle strain. These non-local factors are poorly investigated in studies about muscle injury aetiology in youth soccer players. Accordingly, this thesis outlines 2 studies. The first study was a theoretical paper and the objective was to describe the capacity and demand model for the understanding of sports injuries. The second study was developed in order to identify the contribution of non-local factors related to increased demand in the thigh area that may influence the occurrence of muscle strain in youth soccer players. For the second study, 102 soccer players were assessed and injuries were recorded over 10 months. Classification and regression tree analysis revealed that factors related to the pelvis, hip and foot contribute to the increased demand in the thigh. Interactions among hip lateral rotators isometric torque, asymmetry of pelvic stability and asymmetry of forefoot alignment were found to be related to the occurrence of thigh muscle strain. In addition, high values of hip lateral rotators torque appear to have a protective effect in this injury. The results of this thesis demonstrate the contribution of non-local factors to the occurrence of thigh muscle strain in youth soccer players.